Glutamate in Male and Female Sexual Behavior: Receptors, Transporters, and Steroid Independence - Chiang, Vic Shao-Chih; Park, Jin Ho (Frontiers in Behavioral Neuroscience, 2020)
The survival of animal species predicates on the success of sexual reproduction. Neurotransmitters play an integral role in the expression of these sexual behaviors in the brain. Here, we review the role of glutamate in sexual behavior in both male and females. These encompass the release of glutamate and correlations with glutamate receptor expression during sexual behavior. Then we present the effects on male and female sexual behavior from applications of glutamate, in addition to antagonists and agonists to different glutamate transporters and receptors. Following from that, we articulate how sexual behavior can separate from the effects of sex steroid hormones and then discuss how glutamate may mediate the effects of this steroid-independent sexual behavior. Finally, we demonstrate the interaction of glutamate with other neurotransmitters to impart sexual behavior. These sexual behavior studies are crucial to engender novel treatments of sexual dysfunction and help us understand the complexity of sexual diversity. In the past decade, we have witnessed the burgeoning of novel techniques to study and manipulate neuron activity, to decode molecular events at the single-cell level, and to analyze behavioral data. They pose exciting avenues to gain further insight into future sexual behavior research. Taken together, this work conveys the essential role of glutamate in sexual behavior in both males and females.